Pengembangan Media Pembelajaran Flipbook Digital Pada Pokok Bahasan Gaya Dan Newton Untuk Meningkatkan Minat Belajar - Lis Suswati (Universitas Nggusuwaru, 2026)
This research aims to produce learning media in the form of Physics Flipbook on style and newton materials through validity, practicality and effectiveness in increasing students' learning interest. Research. This research is research and development (R&D) with the research method used by the ADDIE model. The research subjects were grade VIII students of SMP which amounted to 30 students. The instruments used were validation sheets, student response questionnaires to measure effectiveness, and student learning interest questionnaires (pre-test and post-test) to measure effectiveness. The results of the study showed that: (1) The validity of the media obtained very valid criteria based on the assessment of material experts (85,67%) and media experts (87,67%); (2) The practicality of the media is on very practical criteria based on the student response questionnaire with an average percentage of 88,75%; and (3) the effectiveness of media has been proven to increase students' interest in learning with an average N-Gain value of 0.68 (medium/effective criterion) where the average learning interest score increased from 52.40 to 84.60. Thus, the Digital Flipbook learning media developed has proven to be practical, practical, and effective for use in learning Physics Science in junior high schools